2023
DOI: 10.3390/nu15194098
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sector Partnerships for Improved Cooking Skills, Dietary Behaviors, and Belonging: Findings from a Produce Prescription and Cooking Education Pilot Program at a Federally Qualified Health Center

Kelly R. Ylitalo,
Kathryn M. Janda,
Reanna Clavon
et al.

Abstract: Participant engagement, psychosocial factors, and dietary behaviors are important components of “Food as Medicine” and cooking education programs. The purpose of this study is to describe a multidisciplinary cooking program at a Federally Qualified Health Center in central Texas. During biannual harvest seasons (2022–2023), patients participated in four or six weekly 1.5 h hands-on cooking classes with shared meals, education, and produce delivery. Pretest–posttest surveys assessed sociodemographic information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…A comprehensive review of thirty-four multidisciplinary nutrition education interventions revealed that incorporating a cooking component, particularly through hands-on cooking classes, consistently led to improved participant food choices and diets [36]. Recent research further validates this conclusion [37][38][39][40]. However, creating delicious, nutritious meals within the constraints of an individual's lifestyle demands more than just the mechanical skills of preparing food and cooking [41].…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of thirty-four multidisciplinary nutrition education interventions revealed that incorporating a cooking component, particularly through hands-on cooking classes, consistently led to improved participant food choices and diets [36]. Recent research further validates this conclusion [37][38][39][40]. However, creating delicious, nutritious meals within the constraints of an individual's lifestyle demands more than just the mechanical skills of preparing food and cooking [41].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of successful nutrition programs that involve culinary education include the Cooking Matters for Adults intervention, which demonstrated efficacy in improving food resource management skills for shopping and cooking healthy meals, as well as self-confidence in low-income participants [ 37 ]. Additionally, a produce prescription and cooking education pilot program at a Federally Qualified Health Center showed improvements in cooking self-efficacy, behavior change strategies for healthy eating, and vegetable intake in racially and ethnically diverse adult participants [ 38 ]. Further, a systematic review investigating the impact of culinary interventions on psychosocial outcomes reported that community-based cooking interventions positively influenced socialization, self-esteem, and quality of life in adults [ 39 ].…”
Section: Introductionmentioning
confidence: 99%